Stratigraphic setting of the type specimen of Carpocrinus arcticus Frest and Strimple from the Late Silurian of Somerset Island, Arctic Canada - Narbonne, Guy M. (Canadian Journal of Earth Sciences, 1977)
The type specimen of Carpocrinus arcticus Frest and Strimple was collected approximately 65 m below the upper boundary of the Read Bay Formation (Member A) at Fury Point, Somerset Island. Associated brachiopods, trilobites, and bryozoans suggest a Ludlovian age for this specimen.